Carbon Stock, Carbon Fraction and Nitrogen Fraction of Soil Under Bamboo (Dendrocalamus asper Back.) and Non-Bamboo Vegetation - Pambayun, Lintang Panjali Siwi; Purwanto, Benito Heru; Utami, Sri Nuryani Hidayah (Universitas Sebelas Maret, 2023)
The type of vegetation and soil organic matter affect the carbon fraction, nitrogen fraction and soil carbon stocks that contribute to the global carbon cycle. Therefore, the calculation of the composition of the fractions in different land covers is very important as a potential indicator of the effect of land management practices on soil organic carbon dynamics and supports the reduction of carbon dioxide (CO2) and soil carbon storage. This research aimed to determine the composition of the carbon fraction, nitrogen fraction and soil carbon stock in different land cover. There were six types of land cover with vegetations of 10-year-old bamboo, 30-year-old bamboo, 50-year-old bamboo, bulrush, a mixture of brushwood and bulrush, and a mixture of Albizia falcataria and brushwood, each of which was sampled three times. Soil samples were used to determine microbial biomass, particulate organic, humic acid, fulvic acid and soil carbon stock. The six land cover types showed significant differences in all fractions and soil carbon stocks. Fifty-year-old bamboo vegetation has the highest carbon storage of 0.029 g g-1 soil. The stable carbon fraction, in the form of humic acid and fulvic acid, in 50-year-old bamboo vegetation is more excellent than that in other vegetation. This study shows that 50-year-old bamboo vegetation has the potential to sequester carbon and store carbon in forms that decompose slowly, namely humic acid and fulvic acid, in the soil for a longer period.